2020
DOI: 10.21037/apm-20-626
|View full text |Cite
|
Sign up to set email alerts
|

An mRNA sequencing analysis of the healing-promoting role of electroacupuncture a in rat skin wound model

Abstract: Background: Many studies have confirmed that electroacupuncture can regulate the body's environment to treat a variety of diseases. However, there are few reports on the mechanism of electroacupuncture therapy for diseases involving skin injury. Transcriptome sequencing can reveal changes in gene expression within cells and the signaling pathways involved. In this study, we used transcriptome sequencing to study the molecular mechanisms by which electroacupuncture promotes the healing of skin lesions.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…9 It has been found that electroacupuncture can stimulate fibroblast proliferation, recombine collagen fibres, promote angiogenesis and regulate the changes in gene expression profile during wound healing, thus accelerating wound repair. 13,14 In the present study, we demonstrated for the first time that electroacupuncture can target lipid metabolism, particularly phospholipid metabolism, to promote the healing of total skin defects in rats. Seventy-three of these 76 differential lipids were reversed after electroacupuncture treatment, suggesting a pullback effect of electroacupuncture on skin tissue metabolism.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…9 It has been found that electroacupuncture can stimulate fibroblast proliferation, recombine collagen fibres, promote angiogenesis and regulate the changes in gene expression profile during wound healing, thus accelerating wound repair. 13,14 In the present study, we demonstrated for the first time that electroacupuncture can target lipid metabolism, particularly phospholipid metabolism, to promote the healing of total skin defects in rats. Seventy-three of these 76 differential lipids were reversed after electroacupuncture treatment, suggesting a pullback effect of electroacupuncture on skin tissue metabolism.…”
Section: Discussionmentioning
confidence: 55%
“…Lipids likewise play an irreplaceable role in maintaining the skin barrier, supporting skin structure, defending against external attacks and pathogenic pathogens and regulating skin inflammation 9 . It has been found that electroacupuncture can stimulate fibroblast proliferation, recombine collagen fibres, promote angiogenesis and regulate the changes in gene expression profile during wound healing, thus accelerating wound repair 13,14 . In the present study, we demonstrated for the first time that electroacupuncture can target lipid metabolism, particularly phospholipid metabolism, to promote the healing of total skin defects in rats.…”
Section: Discussionmentioning
confidence: 99%
“…EA used a pair of needles so that the impulses could pass from one needle to another as described in previous studies ( 24 ). The negative electrode was attached to wound sites, which are considered the main point, while the positive electrode was attached to a secondary point ( 25 ). The positive and negative electrodes were demonstrated in Figure 6 with a red arrowhead and a black arrowhead, respectively.…”
Section: Methodsmentioning
confidence: 99%